EFFECTIVENESS OF TUTORING PROGRAM (PT) RESULTS IN ACADEMICALLY AT-RISK STUDENTS (ARA) IN THE SCENARIO OF SOCIAL DISTANCING DUE TO COVID-19 AT THE FACULTY OF INDUSTRIAL AND SYSTEMS ENGINEERING (FIIS) OF THE NATIONAL UNIVERSITY OF ENGINEERING (UNI) THROUGH STATISTICS PROCESSED BY THE PROPENSITY SCORE MATCHING (PSM) METHOD (LACCEI, 2024)
A vast literature suggests that investment in education has implications for economic growth, especially in the long term. In this work, we explore the impact of a university program on students' academic performance, specifically the impact of the Tutoring Program on students' average grade in a regular academic cycle, under scenarios of social distancing (COVID-19). To evaluate the impact, the Propensity Score Matching methodology was considered, considering different matching techniques between treatment groups and control groups. It is concluded that in the absence of the Tutoring Program, the impact on students' average grade would be negative. Additionally, the methodology allowed us to consider students' intrinsic variables, thus evidencing that academically at-risk students can improve their average grades per cycle by approximately four points if they are part of the program.